2020
DOI: 10.1590/1678-4685-gmb-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne Syndrome: The many challenges and approaches to understand a multifaceted disease

Abstract: The striking and complex phenotype of Cockayne syndrome (CS) patients combines progeria-like features with developmental deficits. Since the establishment of the in vitro culture of skin fibroblasts derived from patients with CS in the 1970s, significant progress has been made in the understanding of the genetic alterations associated with the disease and their impact on molecular, cellular, and organismal functions. In this review, we provide a historic perspective on the research into CS by revisiting semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 201 publications
(266 reference statements)
0
31
0
Order By: Relevance
“…the Li Fraumeni's syndrome (LFS), caused by the heterozygous mutations of p53 [14] is associated with cancer proneness but not with significant post-radiotherapy adverse tissue reactions [14]; • the ataxia telangiectasia (AT) caused by the homozygous mutations of ATM [15] is associated with post-radiotherapy fatal reactions and AT patients are at high risk of leukemia [15,16]; • the Cockayne's syndrome (CS) caused by the homozygous mutations of the CS genes [17] is associated with a significant tissue radiosensitivity but no cancer proneness [17,18].…”
Section: The Evidence Of a Molecular Differencementioning
confidence: 99%
“…the Li Fraumeni's syndrome (LFS), caused by the heterozygous mutations of p53 [14] is associated with cancer proneness but not with significant post-radiotherapy adverse tissue reactions [14]; • the ataxia telangiectasia (AT) caused by the homozygous mutations of ATM [15] is associated with post-radiotherapy fatal reactions and AT patients are at high risk of leukemia [15,16]; • the Cockayne's syndrome (CS) caused by the homozygous mutations of the CS genes [17] is associated with a significant tissue radiosensitivity but no cancer proneness [17,18].…”
Section: The Evidence Of a Molecular Differencementioning
confidence: 99%
“…Cockayne syndrome (CS) is characterized by a broad spectrum of clinical features including cachectic dwarfism, cutaneous photosensitivity, microcephaly, growth and developmental abnormalities, neurological and retinal degeneration, physical impairment, deafness and premature aging (reviewed in [ 61 ]). Analyses of large cohorts of CS patients have shown that there is no definite correlation between the genotype (mutations identified) and the symptomatology (clinical manifestations) [ 62 , 63 ]. In fact, as far as CSB mutations are concerned, neither the affected region nor the nature of the mutation is linked to specific clinical manifestations or to the severity of the disease, although a tendency to more severe phenotypes has been proposed in patients with mutations downstream of the PiggyBac insertion in intron 5 [ 62 ].…”
Section: Csb In Pathologymentioning
confidence: 99%
“…Fibroblasts from WS patients accumulate protein aggregates and exhibit a dramatic upregulation of autophagy (Talaei et al 2013). Cockayne syndrome (CS) is another severe progeroid disorder, caused by mutations in the transcription-coupled nucleotide excision repair (TC-NER) genes CSA or CSB (Vessoni et al 2020). A recent study showed that CS patient-derived cells exhibit increased levels of misfolded proteins and ER stress, postulated to result from a reduced ribosomal translation fidelity (Alupei et al 2018).…”
Section: Genome Maintenance Defects Are Causally Linked To a Loss Of mentioning
confidence: 99%